High-intensity focused ultrasound ablation as an adjuvant surgical salvage procedure in gestational trophoblastic neoplasia chemotherapy with chemoresistance or recurrence: two case reports - Chaokun She (Taylor & Francis Group, 2021)
Background Chemotherapy is the main treatment strategy for gestational trophoblastic neoplasia (GTN). Surgical resection is crucial to deal with chemoresistance and recurrence following chemotherapy. The aim of this study was to explore if high-intensity focused ultrasound (HIFU) can be used as a complementary technique to surgical procedures in the management of GTN. Case report This case report described two females who previously developed chemoresistance or recurrence during chemotherapy and then underwent HIFU as an adjuvant surgical salvage procedure. For high-risk GTN patients with chemoresistance, HIFU treatment decreased the risk of chemoresistance and shortened the course of chemotherapy. It also reduced the dosage of chemotherapeutic agents used for the patient who suffered a recurrence. Conclusion For patients with GTN who desire to preserve their uterus, HIFU may be used as a complementary technique to surgical resection in the management of GTN.